Redefining Marriage Tahlil Perspective of the Imam Mazhab - Rahman Gea, Afifah; Salam, M. Qodri (Yayasan Salam Cerdas Al-Fattah, 2024)
This paper aims to outline the views of the imams of the madhhab regarding the concept of nikah tahlil, which is one of the controversial issues in Islamic law. Using the literature study method, this study collects primary sources from books by imams of madhhab as well as secondary data from journal articles and books. The results of the study show that nikah tahlil has become a debate among scholars of madhhab, both Shafi'i, Maliki, Hanafi, and Hanbali, each of whom has an understanding based on clear postulates and arguments of legal principles. This paper emphasizes that the practice of tahlil marriage should be avoided, because the majority of scholars (jumhur) recommend the prohibition of this form of marriage. Thus, it is hoped that the results of this study can contribute to the development of Islamic law and public understanding of the issue of tahlil marriage.